A comparison of total intravenous anaesthesia using propofol with sevoflurane or desflurane in ambulatory surgery: systematic review and meta‐analysis. (22nd May 2014) - Kumar, G.; Stendall, C.; Mistry, R.; Gurusamy, K.; Walker, D.
Summary With the popularity of ambulatory surgery ever increasing, we carried out a systematic review and meta‐analysis to determine whether the type of anaesthesia used had any bearing on patient outcomes. Total intravenous propofol anaesthesia was compared with two of the newer inhalational agents, sevoflurane and desflurane. In total, 18 trials were identified; only trials where nitrous oxide was administered to, or omitted from, both groups were included. A total of 1621 patients were randomly assigned to either propofol (685 patients) or inhalational anaesthesia (936 patients). If surgical causes of unplanned admissions were excluded, there was no difference in unplanned admission to hospital between propofol and inhalational anaesthesia (1.0% vs 2.9%, respectively; p = 0.13). The incidence of postoperative nausea and vomiting was lower with propofol than with inhalational agents (13.8% vs 29.2%, respectively; p < 0.001). However, no difference was noted in post‐discharge nausea and vomiting (23.9% vs 20.8%, respectively; p = 0.26). Length of hospital stay was shorter with propofol, but the difference was only 14 min on average. The use of propofol was also more expensive, with a mean (95% CI) difference of £6.72 (£5.13–£8.31 (€8.16 (€6.23−€10.09); $11.29 ($8.62–$13.96))) per patient‐anaesthetic episode (p < 0.001). Therefore, based on the published evidence to date, maintenance of anaesthesia using propofol appeared to have no bearing on the incidence of unplanned admission to hospital and was more expensive, but was associated with a decreased incidence of early postoperative nausea and vomiting compared with sevoflurane or desflurane in patients undergoing ambulatory surgery.